2019
DOI: 10.1101/826917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Collective MAPK Signaling Dynamics Coordinates Epithelial Homeostasis

Abstract: 12Epithelial tissues are constantly challenged by individual cell fate decisions while 13 maintaining barrier function. During oncogenesis, mutant and normal cells also differ in their 14 signaling states and cellular behaviors creating competitive interactions that are poorly 15 understood. Here we show that the temporal patterns of MAPK activity are decoded by the 16 ADAM17-EGFR paracrine signaling axis to coordinate migration of neighboring cells and promote 17 extrusion of aberrantly-signaling cells. Concu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…We then imaged single-cell ERK dynamics in stage 1 acini using 3D confocal spinning disk microscopy of both the H2B and ERK KTR channels with time resolutions of 3 -5 minutes, until acini started to suffer from phototoxicity (which was observed after 10 -23 hours of imaging). Visual inspection of micrographs of stage 1 acini revealed that different cells displayed asynchronous ERK pulses ( Figure 2A) as previously observed in 2D cultures (Aikin et al, 2020;Albeck et al, 2013;Gagliardi et al, 2020). To quantify single-cell ERK activity trajectories, we used a custom-modified version of the opensource LEVER software (Wait et al, 2014;Winter et al, 2016) to segment and track nuclei based on their H2B signal; and to extract ERK activity trajectories by calculating the ratio of the ERK KTR intensities in the nucleus over a voxel mask around the nucleus ( Figure 2B).…”
Section: Stage 1 Proliferative Acini Exhibit Spontaneous Egfr-dependesupporting
confidence: 80%
“…We then imaged single-cell ERK dynamics in stage 1 acini using 3D confocal spinning disk microscopy of both the H2B and ERK KTR channels with time resolutions of 3 -5 minutes, until acini started to suffer from phototoxicity (which was observed after 10 -23 hours of imaging). Visual inspection of micrographs of stage 1 acini revealed that different cells displayed asynchronous ERK pulses ( Figure 2A) as previously observed in 2D cultures (Aikin et al, 2020;Albeck et al, 2013;Gagliardi et al, 2020). To quantify single-cell ERK activity trajectories, we used a custom-modified version of the opensource LEVER software (Wait et al, 2014;Winter et al, 2016) to segment and track nuclei based on their H2B signal; and to extract ERK activity trajectories by calculating the ratio of the ERK KTR intensities in the nucleus over a voxel mask around the nucleus ( Figure 2B).…”
Section: Stage 1 Proliferative Acini Exhibit Spontaneous Egfr-dependesupporting
confidence: 80%
“…Moreover, it is very difficult at this stage to connect the perinuclear relocalisation of actin with the convergent movement of cells. Interestingly, these waves share many similarities with a recent description of ERK waves observed in vicinity of apoptotic cells and BRAF transformed cells [19]. ERK waves also trigger collective movements toward the transformed cells which drive their apical extrusion.…”
Section: Main Textsupporting
confidence: 78%
“…3C, S4A-I). These results suggest that ERK/Akt waves depend on MMP-mediated cleavage of pro-EGF ligands (Dong et al 1999;Aikin et al 2019) (summarized in Fig. 3D).…”
Section: Erk/akt Waves Are Triggered Through Paracrine Egfr and Mmp Smentioning
confidence: 72%